Towards a model of guidance for the democratization of education - Bautista, Hilaria Suzette C. (Animo Repository, 1984)
The identifies and analyzes the guidance services in four selected Paulinian colleges in the Philippines within the framework of equalization of educational opportunities, namely: equality of access, equality of content and equality of results as a step towards the development of a framework for guidance model. The descriptive analytical method was employed in the study. Data were gathered from interviews with guidance directors/counselors and supplemented by other sources like guidance reports and manuals, college handbooks and findings from the related literature and studies. Some of the significant findings of the study were: the abscence of clearly stated objectives by the schools which assure students better and more chances of entering or availing themselves of their educational services three schools follow a highly selective system of admission which is reflected in their admission requirements and procedures while only one has adopted the open-amission-selective-retention policy wherein all students who are duly qualified to enter into tertiary education can have equal chances of access into the college some schools deliver a relatively greater number of services comprising activities which include individual analysis, information, testing, counseling, group guidance, career development, support services, remedial service and regular evaluations and all the schools surveyed have provisions for a placement service through which their graduates are given chances to avail themselves of employment opportunities. It has been concluded that the goals and objectives of the guidance programs under study are closely related to the goal of equalization of educational opportunities in so far as they consciously seek for the development of students' abilities towards maximum academic achievement. All the schools under study profess goals and objectives which are consciously directed to and heavily concentrated on the pursuit of just one particular dimension of equalization of educational opportunity, namely, that of equality of content. Through the activities of the career development service and placement service, opportunities for employment are extended to college graduates.Among the recommendations are the inclusion of provisions of guidance program goals and objectives for the consious pursuit of the goal of equalization of educational opportunities; the implementation of corrective measures in the goals, admission programs and requirements to enable the majority of the students to gain equal access into college; the improvement of the quality of guidance service by adopting more efficient methods of equalizing content through systematic planning and evaluation and the provision of madequage resources; the systematic oraganization of placement programs to facilitate the efficient and maximun utilization of college graduates through the establishment of effective linkages between the education sector and the labor and business industries; and that further research be conducted towards formulation of a guidance program model which full aims at and implements the goal of maximum equalization of educational opportunities so as to ensure for the majority of our student population all the chances for a better life and social mobility through formal tertiary education.